Coral recruitment on concrete blocks at Gosong Pramuka, Kepulauan Seribu, Jakarta. (January 2020) - Subhan, B; Hudhayani, N N; Ervinia, A; Santoso, P; Arafat, D; Khairudi, D; Soedharma, D; Dhere, R M; Madduppa, H
Abstract: The current research was conducted to study the coral recruitment on concrete blocks at Gosong Pramuka, in Kepulauan Seribu. The concrete blocks were observed based on the wave exposure, i.e. the exposed area and sheltered area. A total of 247 coral recruits colonies was recorded on concrete substrates in Gosong Pramuka. The number of coral colonies in the exposed area (210 colonies) was higher than in the sheltered area (37 colonies). Coral recruit density in the exposed area was 1.37 colony/m 2 and in the sheltered area was 0.23 colony/m 2 . A total of four genera was observed in these areas ( Acropora, Porites, Montipora, and Pavona ). The branching Acropora colonies were predominant for both areas, while encrusting non-Acropora was primarily found in the exposed area and massive non- Acropora was the major colonies in the sheltered area. The coral size of branching and encrusting Acropora in the sheltered area was significantly bigger than in the exposed area ( P <0.05). In the exposed area, corals are found in the center of the concrete, but in the sheltered area, they are located in the corner and the edge of the concrete.